Prospects of Islamic Financial Services towards Sustaining Nigerian Economy - Adenigba, Sikiru Atanda; OLAITAN, ABDULKABIR OLADAPO (Al-Basirah Journal, 2022)
Nigeria is deemed as Africa’s largest economy with numerous wealth, bounties, and a plethora of resources. But the fact that many Nigerians still live in drastic poverty has raised concerns among scholars and researchers. The Nigerian economic sustainability records low growth due to corruption which is inflicted by dealings in interest, gambling, and other unethical conducts. Therefore, this paper aims at investigating the prospects of Islamic Financial Services in the Nigerian economic sustainability. The paper also explores Islamic financial services and how they can be used for their purposes. The study finds that many Nigerian citizens see the Islamic financial institutions as ordinary religious organisations that only cater for the welfare of the Muslim populace. It also finds that the Nigerian government pays little spotlight to Islamic financial industries in comparison to its conventional counterpart as a way to sustain the economy. The paper, therefore, concludes that Islamic financial services could be employed to rescue the current situation of the Nigerian economy if properly supervised and utilized. The paper recommends that the Nigerian government should fortify and key into the operations of Islamic financial institutions as these will bring about an equitable distribution of income and resources, poverty alleviation, and discovery of employment opportunities in the country.